Work ethics and organizational performance in Nigeria’s public service - Azuka Nwachuku; Onofere Princewill Okereka; Akpomuvire Mukoro (Qualitative Research of Business and Social Sciences, 2025)
This study examined the relationship between work ethic and organizational performance in the public service sector, with particular emphasis on Nigeria’s public service. A qualitative approach was used for the study. The findings suggest that ethical practices establish a foundation of trust, motivation, and collaboration, all of which contribute to improved service delivery and productivity. The study concludes that work ethic is essential for achieving long-term organizational success and recommends that public service organizations prioritize ethical training, establish ethics advisory boards, and reward ethical behavior to ensure high performance. The study emphasizes the importance of consistently prioritizing workplace ethics to foster a positive work culture, minimize inefficiencies, and improve public sector service delivery.